Analysis of a Massive Open Online Course (MOOC) with an Atypical Terminal Efficiency - Aleman de la Garza, Lorena; Sancho-Vinuesa, Teresa; Gómez Zermeño, Marcela Georgina (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
Massive Open Online Courses (MOOCs) have generated great expectations since they empower online education by providing students, teachers and the community in general, a new way of building knowledge. However, when measuring the efficiency of the MOOCs there is no consensus on the methodology to calculate how successful they are. This document presents a comparative analysis between 12 MOOCs from different academic areas taught by one Latin-American University, who is a pioneer in offering education through the Coursera platform. Within the analysis, we highlight a MOOC with a completion rate exceeding 20%. In order to identify the factors that influenced the atypical completion rate the results include a description of the participants’ characteristics, their access and management of technology as well as the strategies implemented by the instructors and academic staff to generate, for participants, a motivating virtual environment of learning. Results suggest that educational institutions must establish criteria for the design and implementation of MOOCs aiming to offer participants qualitycontent and enriching experiences.